(Invited) Measurement of the Energy-Band Relations of Stabilized Si Photoanodes Using Operando Ambient Pressure X-ray Photoelectron Spectroscopy. (13th April 2015) - Richter, Matthias Hermann; Lichterman, Michael Frankston; Hu, Shu; Crumlin, Ethan J; Mayer, Thomas; Axnanda, S; Favaro, Marco; Drisdell, Walter; Hussain, Z; Brunschwig, Bruce; Lewis, Nathan S.; Liu, Z; et al.
Abstract : The energy-band relations and electronic properties for the light absorber/protection-layer stack of TiO2 -stabilized Si photoanodes have been determined by ambient pressure x-ray synchrotron radiation photoelectron spectroscopy under an applied potential ( operando ), from single core-level emission lines. The experiments have also been complemented with laboratory-based monochromatic XPS data. Electrochemical parameters are additionally derived directly from x-ray photoemission data, and a method is presented to derive interface-state densities from such operando data.